APPLICATION OF ZAKAT AND WAQF AS A TOOL FOR YOUTH EMPOWERMENT IN NORTH-EASTERN NIGERIA - Adamu Abubakar Muhammad; Abubakar Idris Talle; Ikilima Abubakar Shariff; Muhammad Bello (Journal of Islamic Management Studies, 2022)
The goal of this study is to investigate the potential application of zakat and waqf as a tool for youth empowerment in north-eastern Nigeria. The two main Islamic financial instruments, Zakat and Waqf, are discussed along with the Islamic Concept of Empowerment, an update on the youth humanitarian crisis, and the rate of unemployment among Muslims in Nigeria’s northeastern states. A qualitative methodology was used in the research as a tool for gathering data through the review of relevant literature as primary sources and interviews with pertinent personnel on the topic from various perspectives as secondary sources. The study’s findings showed that unemployment has increased the rate of poverty among young people in the study area, and that numerous government and non-governmental organizations’ efforts to eradicate poverty have failed because they have not addressed the issue of the region’s intentionally disempowered youth. It also revealed that insurgency and poverty are the main side effects of societal development in North-Eastern Nigeria and the main causes of the region’s conflict.